EUFEMISME DALAM ARTIKEL POLITIK DAN EKONOMI PADA HARIAN KEDAULATAN RAKYAT - Roswita Lumban Tobing (Jurnal Penelitian Humaniora, 2001)
Abstract The objective of this article is to describe the use of euphemism at “Kedaulatan Rakyat” newspaper. The object of this study is the form of sentences in the field of politics and economics, because a lot of euphemism applied on the both fields. According to the analysis of the data, in appoint of view of its function in the sentences, the form of euphemism has an important role. According to its context, there is euphemism dependent on its context and independent. Keywords: euphemism, context, sentence, function